2015
DOI: 10.1016/j.ecresq.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effortful control and early academic achievement of Chinese American children in immigrant families

Abstract: a b s t r a c tThe present study examined the direct and indirect relations of family contextual factors, effortful control (EC), and the early math and English literacy skills of first and second-generation Chinese American immigrant children in early elementary school. Using a socioeconomically diverse sample of 258 Chinese American children (53% receiving free-or reduced-price school lunch), we assessed EC with a combination of parent and teacher reports, computerized neuropsychological tests, and a behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 80 publications
5
36
1
Order By: Relevance
“…Performance on our test of cognitive control proved to be an effective predictor of tic severity among patients, even when controlling for ADHD, thereby highlighting the fact that TS affects both cognitive and motoric functions. This finding is relevant for patients’ academic performance, given a prior study showing that better performance on this task is associated with better math and literacy skills in childhood ( 46 ). Blink rate was marginally negatively related to tic severity, contrary to expectations.…”
Section: Discussionmentioning
confidence: 69%
“…Performance on our test of cognitive control proved to be an effective predictor of tic severity among patients, even when controlling for ADHD, thereby highlighting the fact that TS affects both cognitive and motoric functions. This finding is relevant for patients’ academic performance, given a prior study showing that better performance on this task is associated with better math and literacy skills in childhood ( 46 ). Blink rate was marginally negatively related to tic severity, contrary to expectations.…”
Section: Discussionmentioning
confidence: 69%
“…Parenting styles and maternal homework help influenced children's reading comprehension and decoding skills and mothers' psychological control highly influenced both maternal help and children's reading comprehension and decoding skills. Previous studies showed that psychological control appears to negatively influence children's school performance (Aunola and Nurmi 2005;Chen, Liu and Li 2000;Chen et al 2014;Coley et al 2011;Ginsburg and Bronstein 1993). Moreover, a warm mother-child relationship encourages and supports children and has a positive relation on children's academic skills (Landry et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fletcher, Walls, Cook, Madison and Bridges (2008) reported that the highest levels of positive academic achievement are linked to authoritative parenting, while the highest levels of social problems in children are linked to authoritarian parenting. Along with permissive parenting, authoritarian parenting has negative effects on school success (Aunola and Nurmi 2005;Chen Main, Zhou, Bunge, Lau and Chu 2014;Coley, Lewin-Bizan and Carrano 2011).…”
Section: Parenting Styles and Children's Academic Skill Developmentmentioning
confidence: 99%
“…Language development as an example of such a low-threshold learning situation has thus been revealed to be linked to temperament and EC in normatively developing monolingual children (e.g., Slomkowski et al, 1992 ). Little is known, however, about the relationship between EC and language competence in dual language learners (DLLs) who acquire the local language as a second language, usually after the age of 3 years ( Winsler et al, 2014 ; Chen et al, 2015 ). Individual differences in the DLL acquisition trajectories have shown a considerable heterogeneity among DLLs (e.g., Kim et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%